Penerapan Metode Show and Tell Serta Memberi Dorongan dan Dukungan Guna Menimbulkan Kepercayaan Diri Anak. - Helga Dilena; Erni Asenli Asbi (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
During development period, children are actively seeking their identity by interacting with their peers both in the real world and in cyberspace. In every aspects of the human personality, self-confidence is an important indicator for one's success in relation to the activities he does. However, there are things that cannot be denied that the level of self-confidence possessed by each individual is different, and this is influenced by other factors besides the process of maturing itself. To generate self-confidence in children at Panti Asuhan Cinta Kasih Medan, activities that can encourage and support children are carried out with the show and tell method which aims to help children achieve their goals, which is referred to as the emergence of self-confidence. With the emergence of self-confidence in children, it will help children show themselves and is good for children's self-development. It is highly expected that this will educate how important it is to help children and provide encouragement and support for children to have self-confidence and be able to express and develop themselves.